Monster hide-and-seek - Scollon, Bill; Mosqueda, Olga T.; Lee, Grace (New York : Random House Children's Books, 2013)
Monster Mike Wazowski searches for all of his friends in the dark as they play a game of hide-and-seek.
At head of title: Disney Pixar Monsters University.
"Glows in the dark"--Cover.
On board pages.
Keywords: Children's stories